EKSEKUSI PUTUSAN TERHADAP PEMELIHARAAN ANAK DALAM PERKARA PERCERAIAN DI PENGADILAN AGAMA - Wulansari, Retno (Jurnal Yuridis, 2015)
The execution verdict against childcare in divorce cases on religious court is not regulated specifically on positive law in Indonesia. The applied rule of law refers to the procedure of verdict execution in civil case on district court as regulated in HIR and RBG. In HIR and RBG provision, the execution objects are fixed or moving objects, while object in verdict execution against childcare is child (human being). In reality, there is no standard legal rule used by judges and judicial officer on the religious court in verdict execution against childcare in divorce cases. therefore, we need written regulations as guidelines for the implementation of this execution. Authors suggest that these regulations are formulated in form of Supreme Court Circular Letter (Surat Edaran Mahkamah Agung - SEMA) or Supreme Court Rules (Peraturan Mahkamah Agung - PERMA). Furthermore, these regulations will be guidance for judges and judicial officers in verdict execution against childcare in divorce cases on religiouscourt.